2020
DOI: 10.1111/imig.12701
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Interstate Migrants in India: A 7 State Policy Evaluation

Abstract: Interstate migration in developing countries is a key income generating strategy for lowincome households. In India, despite the importance of migration between states, interstate migrants continue to face significant integration barriers in their destination states. The impact of state borders on migration within India is significant and large. This study presents one of the first attempts at creating a set of indicators to understand the role of state-level policies for the integration of interstate migrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Based on the migrant labourers’ caste, class identity, and state of origin, they experienced brazen exploitation in regions where they migrate (Shah & Lerche, 2020; Yadav, 2020). Aggarwal et al (2020) observed disparate labour policies among Indian states and the absence of standardised policies leave migrants open to exploitation. We used MIF (McKnight et al, 2018) to analyse the experiences of interstate migrant labourers in India and evaluate crisis management during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the migrant labourers’ caste, class identity, and state of origin, they experienced brazen exploitation in regions where they migrate (Shah & Lerche, 2020; Yadav, 2020). Aggarwal et al (2020) observed disparate labour policies among Indian states and the absence of standardised policies leave migrants open to exploitation. We used MIF (McKnight et al, 2018) to analyse the experiences of interstate migrant labourers in India and evaluate crisis management during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…Governments must address issues affecting migrant labourers by implementing comprehensive national programmes to provide financial, health, social security, and food security (Summerton, 2020). Local governments and federal administration should collaboratively consider problems faced by migrant labourers through different lenses and provide suitable short- and long-term plans to support them (Aggarwal et al, 2020). Governments need to thoroughly review their crisis response plans and prepare for any direct and indirect impact on vulnerable populations purely depending on daily wages (Julka, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the sake of comparability, we decided to focus only on set of indicators/indexes on national policies for international immigrants and emigrants, although a few indexes have emerged on internal migrants and/or local integration policies (e.g. Aggarwal et al, 2020; Manatschal, 2011). Since this article is the first to analyse those topics for such a number of indexes, it is exploratory in nature.…”
Section: Methodsmentioning
confidence: 99%